Soluble tumour necrosis factor-alpha receptor improved the function, hypertrophy, and granular sparkling appearance of the left ventricular myocardium in systemic amyloid A amyloidosis: a case report. Issue 3 (16th March 2020) - Miyagawa, Sawa; Miyamoto, Tadashi; Sato, Yukihito
Abstract: Background: About 7% of amyloid A (AA) amyloidosis cases are accompanied by heart disease. Although several studies have recently reported that specific biologicals improved renal function in AA amyloidosis, little evidence is available regarding heart disease in AA amyloidosis. Case summary: A 57-year-old woman with rheumatoid arthritis presented with sudden worsening of renal function. Echocardiography revealed granular sparkling appearance in the ventricular septum and posterior wall (PW). Echocardiography indicated left ventricular (LV) diastolic dysfunction. Global longitudinal strain (GLS) exhibited an apical sparing pattern. Cardiac biopsy demonstrated amyloid A deposition on immunostaining. Soluble tumour necrosis factor-alpha receptor etanercept therapy was initiated. Four years later, echocardiography showed improved diastolic function, including E / A and E / e ', and decreased wall thickness in both the interventricular septum and PW of the left ventricle. Granular sparkling appearance had diminished. Moreover, the LV dysfunction improved on GLS. Five years later, the medication was gradually losing effect and the patient had worsening pain in the joints; moreover, articular destruction was observed on radiography. The patient was switched to abatacept therapy. Echocardiography showed recurrence of LV hypertrophy and electrocardiogram showed down-sloped ST depression in V4–6 leads. Discussion: This case indicates that etanercept can be effective for heart disease in AA amyloidosis. Of particular, interest is the improvement of granular sparkling appearance in addition to cardiac function improvement noted in this case.